EKSPLORASI ETNOMATEMATIKA TENUN TUAKEPA FLORES TIMUR DAN PENERAPANNYA DALAM PEMBELAJARAN MATEMATIKA - Alfonsus Simon Doweng; Jonner Nainggolan; Ronaldo Kho (Journal of Education Papua Baru, 2025)
Abstract: This analytical ethnographic study aims to explore the ethnomathematical principles embedded in Tuakepa ikat weaving, East Flores, and to formulate its didactical articulation as a learning resource for formal school mathematics. Qualitative data were gathered through in-depth interviews, passive participant observation, and macro-visual documentation of two key weavers selected purposively based on inclusion criteria of specialized expertise until exploratory data saturation was reached. The interactive qualitative data analysis was integrated with the taxonomic framework of Alan Bishop’s six fundamental mathematical activities. Empirical findings demonstrate that all stages of communal production and the morphology of traditional tools encompass the activities of counting, measuring, designing, locating, and explaining. Within the diverse decorative motifs of the cloth, visual representations of plane polygons specifically rhombuses and triangles arallel lines, and invariant translational transformations of the cloth's lane patterns were identified. These findings have practical implications as structured problem contexts based on Realistic Mathematics Education (RME) aimed at accelerating students' Higher-Order Thinking Skills (HOTS) while preserving the communal indigenous mathematics heritage of the local region. Keywords: Geometric Shapes, Ethnomathematics, Mathematics Education, Tuakepa Weaving.   Abstrak: Penelitian etnografis analitis ini bertujuan mengeksplorasi kaidah etnomatematika tenun ikat Tuakepa, Flores Timur, dan merumuskan artikulasi didaktisnya sebagai sumber belajar matematika sekolah formal. Data kualitatif dihimpun melalui wawancara mendalam, observasi partisipatif pasif, dan dokumentasi makro visual terhadap dua penenun kunci yang dipilih secara purposive berdasarkan kriteria inklusi kepakaran khusus hingga mencapai saturasi data eksplorasi. Analisis data kualitatif interaktif diintegrasikan dengan kerangka kerja taksonomi enam aktivitas matematis fundamental menurut Alan Bishop. Hasil penelitian empiris membuktikan seluruh tahapan produksi komunal dan morfologi perkakas tradisional memuat aktivitas membilang, mengukur, merancang, menentukan lokasi, serta menjelaskan. Pada ragam motif hias kain ditemukan representasi visual poligon datar berupa belah ketupat dan segitiga, kedudukan garis sejajar, hingga transformasi translasi invarian pola lajur kain. Temuan ini berimplikasi praktis sebagai konteks masalah terstruktur berbasis Realistic Mathematics Education (RME) guna menakselerasi kompetensi kognitif tingkat tinggi (HOTS) siswa sekaligus melestarikan warisan pengetahuan pribumi (indigenous mathematics) komunal daerah setempat. Kata kunci: Bangun Geometri, Etnomatematika, Pembelajaran Matematika, Tenun Tuakepa.